2014
DOI: 10.9790/2380-07618389
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Study of Reproductive Performances of Indigenous Rams in Bangladesh

Abstract: 10.0±0.4(kg), 3.2±0.1, 18.6±0.7(cm), respectively. The volume, density, mass motility, concentration were 1.2±0.0ml, 2.9±0.0, 4.3±0.0 and 4.1±0.7x10 9 , respectively. The rate of motility: 89. 0±0.2, 72.4±0.2, 62.0±0.6, viability: 91.8±0.1, 75.6±0.2, 64.8±0.6, functional integrity: 87.3±0.2, 69.1±0.2, 50.2±0.5 and normal spermatozoa were 94.0±0.1, 77.3±0.1 and 75.0±0.2 in fresh, chilled and frozen semen, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
1
1
2
Order By: Relevance
“…Sperm motility is a reliable indication of sperm viability (Jha et al, 2018). Sperm motility from this study is higher than the range of 60-85% reported by Khalifa et al (2013), Azizunnesa et al (2014), andJha et al (2018). The higher motility observed from this study could be attributed to the fact that semen collection was made on growing Yankasa rams for the first time and the experimental diet rams were placed on was nutritionally balanced.…”
Section: Semen Characteristicscontrasting
confidence: 72%
“…Sperm motility is a reliable indication of sperm viability (Jha et al, 2018). Sperm motility from this study is higher than the range of 60-85% reported by Khalifa et al (2013), Azizunnesa et al (2014), andJha et al (2018). The higher motility observed from this study could be attributed to the fact that semen collection was made on growing Yankasa rams for the first time and the experimental diet rams were placed on was nutritionally balanced.…”
Section: Semen Characteristicscontrasting
confidence: 72%
“…Although the results indicate a high correlation between the ram semen characteristics. [17,18], suggested that there is no significant correlation between the HOST and other characteristics in the goat semen.…”
Section: Discussionmentioning
confidence: 99%
“…Konsentrasi spermatozoa domba Waringin yang diperoleh dalam penelitian ini rata-rata berkisar antara 2.186,67 ± 319,74 juta sperma/ml. Nilai ini sebanding dengan konsentrasi spermatozoa domba yang dilaporkan oleh Jha et al [19] yaitu berkisar antara 2.644,4 ± 555,9 -3.628,1 ± 654,1 juta sperma/ml, meskipun lebih rendah dari laporan Azizunnesa et al [20] yakni antara 4,8 ± 1,8 -5,4 ± 1,9x10 9 sperma/ml.…”
Section: Pembahasanunclassified
“…Motilitas rata-rata spermatozoa segar domba Waringin yang diperoleh yaitu 66,68 ± 5,43%. Jha et al [19] melaporkan bahwa domba jantan memiliki 60,0 ± 9,0 -87,0 ± 2,7% spermatozoa motil, namun juga lebih rendah dari laporan Azizunnesa et al [20]. Adapun persentase viabilitas spermatozoa domba Waringin yang diperoleh pada penelitian ini yaitu sebesar 67,39 ± 5,99%.…”
Section: Pembahasanunclassified